Increase of safety of electric energy usage in coal mines - Мнухин, Анатолий Григорьевич; Иорданов, Игор Вячеславович (Technology audit and production reserves, 2015)
The work is devoted to the creation of ultrafast device for protecting electrical networks in hazardous industries, such as coal mines, from the emergency operation of short circuit. For response time to ensure the unit up to 100 microseconds, as the drive of the contact group was used electro effects - electric emplosion. Switching devices such working one-sticks, until recently was not in the world practice. The results will help to reduce the probability of occurrence in coal mines dangerous on gas and dust of man-made accidents (explosions and fires), with heavy technical and social consequences. In addition, a similar device can be effectively used in the chemical, petrochemical and other industries in which the possible presence of an explosive or the environment.